Material didáctico lúdico para la enseñanza aprendizaje del cuerpo humano - Mite Sanchez Gilda Esthefania; Mendoza Guillen Andrea Estefania (Machala, 2022)
The didactic materials are important for the development of a quality education, considering that motivation is essential to teach and learn, it is totally necessary to apply new teaching methodologies to achieve an efficient change in education, it is important for the development of a quality education, considering that motivation is essential to teach and learn, it is totally necessary to apply new teaching methodologies to achieve an efficient change in education, In order to do so, it is necessary to have teachers fully trained in the application of these didactic materials, since for most teachers it is very complicated to apply new teaching methodologies, taking into account teachers from a generation in which classes were taught in a monotonous way by means of textbooks, The challenges in education are one of them, that is why it has been necessary to carry out a research about the didactic and ludic material for the teaching and learning of the human body, third grade, school "Luis Ángel León", canton of Pasaje, 2021-2022. The topic was selected by means of the direct observation that took place in the aforementioned institution. The research is being related to the quantitative-qualitative approach, given to the previous obtaining of field information which was tabulated and presented through statistical graphs, these data are obtained through the survey to the 21 students and interview to 2 teachers and an observation guide to the teaching-learning process, It should be emphasized that these techniques and instruments were applied in order to obtain clear results about how the teaching and learning process has been developing in the area of Natural Sciences. In the face of the problem exposed, knowledge was obtained about the lack of application of playful didactic materials, for this reason it was decided to elaborate materials related to innovative practical handicrafts, such as didactic models in order to make a monotonous class more dynamic, participatory and innovative. Finally, it is clear that in order to have an educational development it is necessary to have a fully trained counselor or with knowledge about the practical crafts to be able to generate a quality transformation in both students and teachers, The collaboration of the parents is also needed, since education starts at home, the values that are taught in the family environment are of utmost importance, since the teacher is the one who shapes the previous knowledge of the students and students need to be motivated and interested in learning more about the composition of the human body being one of the most important subjects because the body is composed of the nervous system, circulatory system, digestive system, muscular system and skeleton, the purpose of the proposal is to obtain a more recreational education that leads to the development of skills, abilities and competences in the educational field, considering that the space where a class is taught is fundamental for learning, because it is the place where the student will acquire knowledge from an early age, which must be used efficiently, which is why the educational institution must require that teachers receive updated information and materials to move towards continuous improvement.
Los materiales didácticos, son importantes para el desarrollo de una educación de calidad, considerando que la motivación es esencial para enseñar y aprender, es totalmente necesario la aplicación de nuevas metodologías de enseñanza para lograr un cambio eficiente en la educación, para ello se necesita de docentes totalmente capacitados en la aplicación de estos materiales didácticos, puesto que para la mayoría de docente es muy complicado aplicar nuevas metodologías de enseñanza teniendo en cuenta docente de una generación en donde las clases se las impartía de manera monótonas la misma que se ha venido dando por textos, pizarra y marcador, son esos unos de los desafíos en la educación, es por ello que se ha visto preciso realizar una investigación acerca de los material didáctico lúdico para la enseñanza aprendizaje del cuerpo humano, tercer grado, escuela “Luis Ángel León”, cantón pasaje, 2021-2022. El tema planteado fue seleccionado por la observación directa a que se dio en la institución ya mencionada. La investigación está siendo relacionada con el enfoque cuanti-cualitativamente, dado a la previa obtención de información de campo la cual fue tabulada y presentada a través de gráficos estadístico, estos datos son obtenido por la encuesta a los 21 estudiantes y entrevista a 2 docentes y una la guía de observación al proceso de enseñanza aprendizaje, cabe recalcar que estas técnicas e instrumentos fueron aplicadas con el fin de obtener resultados claros acerca de cómo se ha estado desarrollando la enseñanza aprendizaje en el área de Ciencias Naturales, ante la problemática expuesta se obtuvo conocimiento de la falta de aplicación de materiales didácticos lúdicos, por eso se optó por la elaboración de materiales, relacionados a las manualidades practicas innovadoras, como las maquetas didácticas con el fin de hacer de una clases monótona más dinámica, participativa e innovadora. Finamente, es claro que para tener un desarrollo educativo se necesita de un orientador completamente capacitado o con conocimientos acerca de las manualidades prácticas para poder generar una transformación de calidad tanto en los estudiantes como en docentes, también se necesita la colaboración de los padres de familia, dado que la educación inicia desde la casa, son de suma importancia los valores que se imparten en el ambiente familiar, puesto que el docente es quien moldea los conocimientos previos de los estudiantes y se necesita de estudiantes motivados e interesado por conocer más acerca de la composición del cuerpo humano siendo una de las materias más importantes porque el cuerpo está compuesto por el sistema nervioso, sistema circulatorio, sistema digestivo, sistema muscular y esqueleto, el propósito de la propuesta es que se obtenga una educación más recreativa que de paso al desarrollo de competencias en el ámbito educativo, considerando que el espacio en donde se imparte una clases es fundamental para el aprendizaje, porque es el lugar en donde el estudiante va a adquirir conocimientos desde una temprana edad, la cual debe ser aprovechada eficientemente, es por ello que la institución educativa debe exigir que los docente reciban una actualización de información, materiales para avanzar a una mejora continua.
Keywords: MATERIAL DIDACTICO; LUDICA; ESTUDIANTE; ENSEÑANZA APRENDIZAJE